Transhepatic implant of a trimmed Melody™ valved stent in tricuspid position in a 1‐year‐old infant. Issue 3 (16th August 2016) - Cools, Bjorn; Rega, Filip; Gewillig, Marc
Abstract : Percutaneous valved stent implantation is precluded in small infants because large delivery sheaths and large devices. We describe a procedure in a 1‐year‐old boy in whom a 19 mm Epic™ valve in tricuspid position had become dysfunctional. As the internal diameter of the prosthetic valve was about 16 mm, the only available valve was the Melody™ valved stent. Technical modifications were required to address issues like venous access, the bulky delivery system, and the length of the valved stent. The Melody™ valved stent was surgically trimmed and mounted on a 16 mm Tyshak balloon, access was provided transhepatically through a short 18 Fr sheath. After deployment, the intrahepatic route was sealed with two vascular plugs (8 and 10 mm) in tandem. The procedure was uncomplicated with perfect valve function 18 months after implant. © 2016 Wiley Periodicals, Inc.